2021
DOI: 10.21037/gs-21-400
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of a type of pancreatitis worthy of attention: acute pancreatitis associated with pancreatic tumors—current problems and future thinking

Abstract: We have newly defined a type of pancreatitis based on clinical practice experience, namely pancreatic tumorassociated pancreatitis (PTP). PTP has many new features in terms of diagnosis and treatment, and it is therefore necessary to describe it in detail.AP has various causes and a complex pathogenesis, and its occurrence and development are affected by many factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The underlying mechanism whereby a tumor may cause AP remains unclear. It is suggested that local pancreatic necrosis caused by tumor growth and direct activation of pancreatic enzymes by neoplastic tissue may be possible mechanisms of AP 9,33 . Apart from that, tumor compression or cancer cell invasion may cause the obstruction of the main pancreatic duct and impede the flow of pancreatic enzymes, which leads to inappropriate enzyme activation within the pancreas 20,33 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The underlying mechanism whereby a tumor may cause AP remains unclear. It is suggested that local pancreatic necrosis caused by tumor growth and direct activation of pancreatic enzymes by neoplastic tissue may be possible mechanisms of AP 9,33 . Apart from that, tumor compression or cancer cell invasion may cause the obstruction of the main pancreatic duct and impede the flow of pancreatic enzymes, which leads to inappropriate enzyme activation within the pancreas 20,33 .…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that local pancreatic necrosis caused by tumor growth and direct activation of pancreatic enzymes by neoplastic tissue may be possible mechanisms of AP. 9,33 Apart from that, tumor compression or cancer cell invasion may cause the obstruction of the main pancreatic duct and impede the flow of pancreatic enzymes, which leads to inappropriate enzyme activation within the pancreas. 20,33 Interestingly, main pancreatic duct involvement (MPDI) has been demonstrated to be an independent poor prognostic factor for PNETs.…”
Section: Comparison Of Baseline Characteristics Between the Ap And Co...mentioning
confidence: 99%
See 2 more Smart Citations